2023
DOI: 10.1126/scitranslmed.adg2887
|View full text |Cite
|
Sign up to set email alerts
|

Long-acting refillable nanofluidic implant confers protection against SHIV infection in nonhuman primates

Abstract: The impact of pre-exposure prophylaxis (PrEP) on slowing the global HIV epidemic hinges on effective drugs and delivery platforms. Oral drug regimens are the pillar of HIV PrEP, but variable adherence has spurred development of long-acting delivery systems with the aim of increasing PrEP access, uptake, and persistence. We have developed a long-acting subcutaneous nanofluidic implant that can be refilled transcutaneously for sustained release of the HIV drug islatravir, a nucleoside reverse transcriptase trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 48 publications
1
4
0
Order By: Relevance
“…Compared with human studies, including the nonerodable ISL implant, we observed lower ISL-TP concentrations at equivalent plasma ISL values [ 15 , 16 , 44 , 45 ]. However, we calculated the ISL-TP:ISL ratios in other macaque studies and found a similar trend of lower ISL-TP in macaques compared to humans [ 14 , 36 , 46 , 47 ]. This could be attributed to differential rates of phosphorylation between species or possibly the sample processing method [ 36 ].…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Compared with human studies, including the nonerodable ISL implant, we observed lower ISL-TP concentrations at equivalent plasma ISL values [ 15 , 16 , 44 , 45 ]. However, we calculated the ISL-TP:ISL ratios in other macaque studies and found a similar trend of lower ISL-TP in macaques compared to humans [ 14 , 36 , 46 , 47 ]. This could be attributed to differential rates of phosphorylation between species or possibly the sample processing method [ 36 ].…”
Section: Discussionsupporting
confidence: 56%
“…Recently, a refillable ISL implant was evaluated as PrEP in both vaginal and rectal SHIV challenge models. Although complete protection was achieved, the ISL levels were well above the limit deemed to be safe in humans [ 46 ]. Next-generation PCL implants releasing ISL at levels that are predicted to be safe were assessed as PrEP in the vaginal SHIV challenge model, and the threshold of protection is very close to the human PrEP benchmark of 50 fmol/10 6 PBMCs [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a monthly dapivirine vaginal ring has been approved for the prevention of HIV in several countries [ 8 ], and other regimens, such as a twice-yearly subcutaneous injection of lenacapavir, have been recently approved [ 9 ]. Long-acting drug delivery technologies such as implants are also under development for HIV PrEP [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…and other regimens, such as a twice-yearly subcutaneous injection of lenacapavir, have been recently approved [9]. Long-acting drug delivery technologies such as implants are also under development for HIV PrEP [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The investigational drug islatravir (ISL, MK-8591 or EFdA) may have considerable potential for LA-PrEP, 1/27 due to its antiviral potency (sub-nanomolar range), long intracellular half-life and high barrier to drug resistance [13,14]. So far, the pharmacokinetics and antiviral potency of ISL have been assessed for daily, weekly and monthly oral dosing, and as a subdermal implant, which may need to be replaced every 3-6 months.…”
Section: Introductionmentioning
confidence: 99%